SOME MEASUREMENTS OF TOXICITY OF TANNERY AND TEXTILE WASTES AND THEIR COMPONENTS TO FISH BY BIO-ASSAYS - David, A; Roy, P (Indian Journal of Fisheries, 2016)
It is only in recent years that attempts have been made to study effects of industrial wastes on the riverine fish resources in India and correctly assess the damage. With an accelerating increase presently in various fields of industrial development, the practice by the factories to dispose the trade wastes and effluents into the nearest stream or river without considering its consequences, will become still more widely prevalent. Every water-shed has its own pollutional load-bearing capacity and if within limits, the river or stream is able to render innocuous the adverse effects by physical, chemical and biological purificatory processes and thus maintain the aquatic life of a stream or river causing no obvious damage. If, however, pollutants are added in large quantities they may seriously alter the environmental conditions for a certain stretch, and the waste may thus affect fish life. Besides a study of the physico-chemical and biological conditions of the aTected stream to evaluate the harmful effects to fish life indirectly, direct experimental evidence is also necessary to ascertain how and in what concentrations such effluents or their constituents kill the fish. By the application of methods of bio-assay, a bio'ogist can easily measure the d'igre^ of toxicty in a material and to what extent it should be diluted or otherwise treated before being added to a stream. Thereby, precise standards for the disposal of each individual industrial waste can be set up more scientifically. Such dilu ions will be favourable not only to fish but also for fish food organisms which find suitable medium to grow and reproduce and provide an optimum fisher op.